The role of optimization to control traffic signals setting on capacity and flow at peak hours at intersections - Jafari Haghighatpour, Pegah; Mansourkhaki, Ali; Mehdizadeh, Gholamreza; Keymanesh, Mahmouddreza (International Journal of Engineering and Technology, 2015)
Control the pre timing of traffic signals has many advantages because of its responsiveness to traffic demands, short cycles, and effective use of capacity leading to and recovering from oversaturation and amenability to aggressive transit priority. Traffic congestion in urban road and freeway networks leads to a strong degradation of the network infrastructure and accordingly reduced throughput, which can be countered via suitable control measures and strategies. Coordination between intersections in a central system increases capacity, appropriate traffic flow and reduce total delays of vehicles. Scats system has been installed in many world intersections, and many researchers have done about the advantages of it to decrease delays and travel times at intersection. SCATS is a modular system and development of this is possible. Now in Tehran's this system is used and traffic conditions matches on it. Traffic signal timing schedule gives in this system as default and although this system is capable of adapting to the moment traffic but in terms of super saturation and during peak hours due to the lack of optimization, default program around intersection has caused widespread congestion at intersection. In this paper, two intersections of East and West of Tehran have been selected, and in two different situations, the flow to capacity ratio of traffic signal timing has been investigated before and after optimization. Simulation by AIMSUN and optimization by SYNCHRO software is done. After optimization can be observed that if before the pre-defined schedule for SCATS, this plan for each intersection of the volume of traffic at peak hours has been optimized, a great reduction in delay and increase in capacity can be observed at intersections. For example, delay time reduction has been occurred about 14.77 in AM peak time and 12.65 in PM peak time at GOLBARG-DARDASHT intersection.